The massage approach of Avicenna in the Canon of Medicine : Avicenin pristup masaži u njegovu djelu Kanon medicine - Çetkin, Murat (Array, 2019)
Massage is the manipulation of the body tissues by using techniques, such as rubbing, kneading, pressing, and rolling to sustain a state of health and wellness. Massage is one of the oldest and most natural healing applications in human history. Avicenna (980 – 1037) gained a very important position in the medical world with his most important work, the Canon of Medicine, known as the holy book of medicine in the Western world. Different types of massage were defined in the book. These were hard friction that braces the body, soft friction that relaxes the body, repeated friction that reduces the amount of fat in the body, moderately hard friction that improves the body, rough friction that leads the blood to the surface rapidly, gentle friction that increases blood flow in the application area, preparatory friction that prepares the body before exercise, and restorative friction that is applied after exercise which alleviates exhaustion. It may be seen that Avicenna, whose work shows influence of Greek and Roman physicians, was heavily influenced by Hippocrates and Galen. It is seen that the massage techniques and effect mechanisms defined by Avicenna about a thousand years ago have contributed a lot to the developments in massage through the historical process.